Socio-Cultural and Ideological Preconditions of Gender Equality - Sviytlana Storozhuk; Ihor Goyan (International Society of Philosophy and Cosmology, 2017)
The article examines the factors that have led to the contradiction between a legislated principle of gender equality and, broadcast from pre-modern by a number of social institutions a social differentiation by gender and discrimination generated by it, existing in modern outlook and socio-cultural life. The article shows that the concepts of natural equality of people and social consensus together with the process of secularization and desecration, developed during the modern period, transformed a social reality, but they usually do not apply to a person who is still viewed through the prism of axiological and ideological premodern paradigm. Thus, the concept of natural equality has extrapolated only to men who were considered carriers of social activity in premodern culture. It is emphasized that despite the radical changes of socio-cultural and political life of European society that occurred as a result of implementation of social modern program, a family, remaining a decentralized nucleus, was living by premodern values that gained social significance at a time when a woman acquired her social activity.